2015
DOI: 10.1155/2015/194894
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MicroRNAs in Cardiac Stem Cells

Abstract: Stem cells are considered as the next generation drug treatment in patients with cardiovascular disease who are resistant to conventional treatment. Among several stem cells used in the clinical setting, cardiac stem cells (CSCs) which reside in the myocardium and epicardium of the heart have been shown to be an effective option for the source of stem cells. In normal circumstances, CSCs primarily function as a cell store to replace the physiologically depleted cardiovascular cells, while under the diseased co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…Collectively, these findings support that up-regulation of miRNA-21 can enhance capacity of Sca-1 + CSCs to repair damaged myocardium by inducing migration and proliferation of Sca-1 + CSCs in vitro , which may pave the way for therapeutic strategies directed toward restoring miRNA-21 function for heart-related diseases. Purvis et al published a review article in which they stated that the use of miRNAs to CSCs to treat myocardial infarction was a newly emerging treatment strategy to regulate the proliferation and differentiation of CSCs [ 13 ]. Menasche et al reported that if the benefit of stem cell transplantation could be recapitulated through the broad administration of their secretome, these stem cells could be exclusively utilized in vitro for producing the factors that would be the only therapeutics given to patients with heart failure [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these findings support that up-regulation of miRNA-21 can enhance capacity of Sca-1 + CSCs to repair damaged myocardium by inducing migration and proliferation of Sca-1 + CSCs in vitro , which may pave the way for therapeutic strategies directed toward restoring miRNA-21 function for heart-related diseases. Purvis et al published a review article in which they stated that the use of miRNAs to CSCs to treat myocardial infarction was a newly emerging treatment strategy to regulate the proliferation and differentiation of CSCs [ 13 ]. Menasche et al reported that if the benefit of stem cell transplantation could be recapitulated through the broad administration of their secretome, these stem cells could be exclusively utilized in vitro for producing the factors that would be the only therapeutics given to patients with heart failure [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there were few studies that investigated the role of miRNA-21 in CSCs, which could restore cardiac function and reduce infarct size after cardiovascular diseases [ 12 ]. Furthermore, Sca-1 + CSCs accounts for 70% of the cells in the mouse heart after the depletion of cardiomyocytes [ 13 ]. Thereby, we hypothesized that up-regulation of miRNA-21 could promote migration and proliferation of Sca-1 + CSCs to enhance the capacity of Sca-1 + CSCs to repair damaged myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…These endogenous CSCs and CPCs, which have been considered as the "next generation" of stem cells, can be derived from the heart tissue itself and hold great promise for cardiac repair (51). Although little is known regarding the control of the CSCs/CPCs functions by miRNAs, several reports have demonstrated that survival of CSCs/CPCs could be enhanced through miRNA modulation (52). Indeed, Liu et al reported that miRNA-155 provides the opportunity to block necrosis, a process traditionally thought to be non-regulated, and might be a potential novel approach to improve cell engraftment during cell therapy (53).…”
Section: Cardiac-derived Stem Cellsmentioning
confidence: 99%
“…Autophagy is a lysosomal degradation process that regulates cellular homeostasis (20). MiRNAs may regulate cardiac stem cell proliferation and differentiation (21) by acting in an autocrine and/or a paracrine fashion (22, 23). MiRNAs encapsulated in an exosome circulate through blood and may have paracrine effects (24).…”
Section: Introductionmentioning
confidence: 99%